ВИКОРИСТАННЯ КОМП’ЮТЕРНОГО МОДЕЛЮВАННЯ У ПРОФЕСІЙНІЙ ПІДГОТОВЦІ СТУДЕНТІВ ЕКОНОМІЧНИХ СПЕЦІАЛЬНОСТЕЙ - Рум’янцева, К. (Збірник наукових праць Уманського державного педагогічного університету, 2019)
У даній статті презентовані теоретичні та прикладні аспекти реалізації упровадження комп’ютерного моделювання до розв’язання творчих фахових завдань студентами економічних спеціальностей під час вивчення дисципліни «Математика для економістів». In the article the following items are considered: the formation of the creative skills for solving professional problems through the using of computer models among potential economists. The terms of organization of the creative activity of students in the process of problem-developing studying are indicated. The conclusions concerning the advantages of using of computer models in the creative study activity among students-economists are made.